Mechanism of glucagon-like peptide-1 receptor agonist in the treatment of obesity and food addiction - LIU Luyao, LI Linwei, WANG Chen, DI Jianzhong (Xin yixue)
Obesity and food addiction have become major threats to public health， and their synergistic interactions exacerbate metabolic abnormalities and comorbidities. Glucagon-like peptide-1 receptor agonist （GLP-1RA） has emerged as a promising therapeutic option for these conditions， and their mechanism of action has become a major research focus. Evidence indicates that GLP-1RA suppress appetite and delay gastric emptying through central and peripheral pathways. Furthermore， they modulate mesolimbic dopamine system （MLDS）， reduce the release of dopamine in the nucleus accumben， attenuate the rewarding effects of high-calorie foods and ameliorate addictive eating behaviors， thereby treating obesity. However， adverse gastrointestinal effects and potential long-term risks of GLP-1RA necessitate cautious clinical management. In this article， recent clinical advances in the application of GLP-1RA applications for the treatment of obesity and food addiction were reviewed， providing reference for drug selection for obesity and food addiction.